The Long-Term Effects of a Housing First Intervention on Primary Care and Non-Primary Care Physician Visits Among Homeless Adults with Mental Illness: A 7-Year RCT Follow-Up. (July 2021) - Mejia-Lancheros, Cilia; Lachaud, James; To, Matthew J.; Lee, Patsy; Nisenbaum, Rosane; O'Campo, Patricia; Stergiopoulos, Vicky; Hwang, Stephen W.
Background: Housing First (HF)-based interventions have been implemented in North America and beyond to help people exit homelessness. The effect of these interventions on access to primary and specialist care services is not well-defined. This study assesses the long-term effects of an HF intervention for homeless adults with mental illness on primary care physician (PCP) and non-primary care physician (non-PCP) visits. Methods: This is a secondary analysis of the At Home/Chez Soi study, a randomized trial of HF for homeless adults with mental illness in Toronto, Canada. High-need (HN) participants were randomized to HF with assertive community treatment (HF-ACT) or treatment as usual (TAU). Moderate needs (MN) participants were randomized to HF with intensive case management (HF-ICM) or TAU. The primary outcomes were the incidence and the number of visits to a PCP and non-PCP over 7-years post-randomization, compared to the 1-year pre-randomization. Results: Of 575 enrolled participants, 527 (80 HN and 347 MN) participants were included in the analyses. HN participants who received HF-ACT had a significant reduction in the number of visits to a PCP compared to TAU participants (ratio of rate ratios (RRR): 0.66, 95% CI: 0.48-0.93) and a significant reduction in the number of non-PCP visits compared with TAU participants (RRR: 0.64, 95% CI: 0.42-0.97) in the 7-years post-randomization compared to the 1-year pre-randomization. MN participants who received HF-ICM had a significant increase in incident visits to a PCP compared to TAU participants (RRR: 1.66, 95% CI: 1.10-2.50). No effect of HF-ICM was observed on the incidence or number of non-PCP visits. Conclusion: HF has differing effects on visits to PCPs and non-PCPs among homeless people with high and moderate needs for mental health supports. HF does not result in a consistent increase in PCP and non-PCP visits over a 7-year follow-up period. The At Home/Chez Soi study is registered with ISRCTN (ISRCTN, ISRCTN42520374).